Hadith About Al-Samahah in Mu'amalah: A Thematic Study of the Book Riyad Al-Salihin - Dede Anggara; Afdilla Nisa (International Journal of Education, Information Technology, and Others, 2026)
Al-samahah (broad-heartedness and ease) in the context of muʿamalah (socio-economic transactions). Amidst contemporary economic practices that are often rigid and exploitative, the value of al-samahah becomes a fundamental ethic that is important to review. This study aims to analyze the understanding and application of al-samahah hadiths in muʿamalah sourced from the book Riyad al-salihin by Imam al-Nawawi. This type of research is library research with a thematic approach (maudhu’i). Primary data was obtained from the book Riyad al-salihin by Imam Nawawi, while secondary data came from books, journals, and other literature that support thematic hadith studies. This research was conducted through the stages of collecting hadiths with the theme of al-samahah, takhrij, and analysis of syarah to obtain a complete understanding. The results of the study show that al-samahah in Riyad al-salihin is a comprehensive spectrum of muʿamalah ethics. These values ​​include: (1) Husn al-Qada' (debtor's professionalism in paying); (2) Samhan attitude (easy and spacious) in the three pillars of transactions: selling, buying, and collecting; (3) Tanfīs (giving grace/restructuring) and Wad' (giving relief/discounts) for those in difficulty; and (4) Al-Tajawuz (clearing debt) as the peak of the creditor's ihsan. This study concludes that these values ​​have highly relevant applications in addressing contemporary muʿamalah challenges, such as in e-commerce ethics, humane fintech collection practices, and debt restructuring policies in financial institutions.